Prevalência e suscetibilidades bacterianas das infecções comunitárias do trato urinário no Hospital Universitário João de Barros Barretos: período de janeiro a dezembro de 2006 - VIANA, Murillo Ferreira (2023)
For effective treatment of urinary infections is necessary to know the prevalence of causing microorganisms and microbial pattern of susceptibility. The objective of this work is to associate urinary infection acquired in the community with epidemiological data, and determine what its mains etiological agents and the pattern of sensitivity of these microorganisms to various antibiotics. Were analyzed urine cultures from 1618 ambulatory patients seen at the University Hospital João de Barros Barreto in 2006. Most of the cultures were requested for females (68,97%). There was no growth in 70,15% and contamined cultures in 15,82% of patients. The majority of contamination occurred in patients aged over 60 years. Urinary tract infection was identified in 227 patients (14,03%), mainly for females (83,70%) and the ages of 3648 years (21,59%) and 4860 years (24,23%). The most frequent etiological agents were Escherichia coli (70,48%) and Klebsiella sp. (13,66%). In relation to the most prescribed antibiotics in clinical practice, the were more susceptibility were to levofloxacin (72,22%), ciprofloxacin (71,01%), norfloxacin (69,70%), amikacin (100%), gentamicin (96,91%) and cefotaxime (94,15%). There was low sensitivity to sulphamethoxazoletrimethoprim (43,01%) and ampicilin (23,81%). It was concluded that the quinolones (ciprofloxacin, levofloxacin, norfloxacin) are the first choice for oral empirical treatment of urinary infections. In parenteral treatment the best results were obtained with the use of aminoglycosides (amikacin, gentamicin) and cefotaxime.